Pand-e Pirān, introducing its manuscripts and its newly rewritten and its Arabic translation - Mahmood Nadimi Harandi; Tahmine Ataei Kachuei (ادبیات عرفانی)
The book of Pand-e Pirān was edited based from a manuscript preserved in the British Museum by Jalāl Matini and published in 1979. Notably, the title of the book, the author’s name, and the date of its composition are not mentioned in the text of the book. In this article, we will first introduce other manuscripts of Pand-e Pirān which are known under the titles of "Mavā`ez al-Ferdows" and "Manāqeb al-Awliyā ". Then, for the first time, we will introduce its rewritten text called "Jame` al-Hekāyāt" which Nasrollāh ibn Shahrollāh Termezi wrote in the 10th or 11th century AH. Of course, because he did not mention anything about the original of the book, but claimed that he collected the anecdotes himself, his work is considered to be plagiarism. In the following, for the first time, we will introduce the Arabic translation of Pand-e Pirān under the name of "Hekāyāt al-Sālehin" and then we will present new information and findings about the original name of Pand-e Pirān and the name of the author and the date of its composition. Finally, by citing examples, we show that using newly known manuscripts, new critical editing of Pand-e Pirān is necessary.